Concise synthesis of rare pyrido[1, 2-a]pyrimidin-2-ones and related nitrogen-rich bicyclic scaffolds with a ring-junction nitrogen. Issue 3 (3rd December 2015) - Alanine, T. A.; Galloway, W. R. J. D.; Bartlett, S.; Ciardiello, J. J.; McGuire, T. M.; Spring, D. R.
Abstract : Pyrido[1, 2- a ]pyrimidin-2-ones and related azabicycles with a ring-junction nitrogen represent attractive structural templates for drug discovery. Abstract : Pyrido[1, 2- a ]pyrimidin-2-ones represent a pharmaceutically interesting class of heterocycles. The structurally related pyrido[1, 2- a ]pyrimidin-4-ones are associated with a broad range of useful biological properties. Furthermore, quinolizinone-type scaffolds of these sorts with a bridgehead nitrogen are expected to display interesting physico–chemical properties. However, pyrido[1, 2- a ]pyrimidin-2-ones are largely under-represented in current small molecule screening libraries and the physical and biological properties of the pyrido[1, 2- a ]pyrimidin-2-one scaffold have been poorly explored (indeed, the same can be said for unsaturated bicyclic compounds with a bridgehead nitrogen in general). Herein, we report the development of a new strategy for the concise synthesis of substituted pyrido[1, 2- a ]pyrimidin-2-ones from readily available starting materials. The synthetic route involved the acylation of the lithium amide bases of 2-aminopyridines with alkynoate esters to form alkynamides, which were then cyclised under thermal conditions. The use of lithium amide anions ensured excellent regioselectivity for the 2-oxo-isomer over the undesired 4-oxo-isomer, which offers a distinct advantage over some existing methods for the synthesis of pyrido[1, 2- a ]pyrimidin-2-ones. Notably, different aminoazines could also be employed in this approach, which enabled access to several very unusual bicyclic systems with higher nitrogen contents. This methodology thus represents an important contribution towards the synthesis of pyrido[1, 2- a ]pyrimidin-2-ones and other rare azabicycles with a ring-junction nitrogen. These heterocycles represent attractive structural templates for drug discovery.